PENDAMPINGAN UNTUK PENINGKATKAN MUTU KINERJA SEKOLAH - Yuyun Nuriah; Dalmeri Dalmeri; Supadi Supadi (Universitas Muhammadiyah Luwuk, 2023)
The quality of public elementary school (SDN) performance is an internal problem that is a significant concern because the performance of schools is not going well, as evidenced by the A accreditation but does not match the school performance based on the results of the quality report card for the last two periods. Assistance to improve the quality of school performance aims to map with an internal quality assurance program to improve the quality of school performance, seen from the eight national standards of education. Assistance is provided through observation, training, interviews, and discussions. The mentoring results showed an increase in the ability to understand and implement the stages of the SPMI cycle at SDN Batu Ampar 06 East Jakarta. After regular mentoring and monitoring every month for six months. It is evident from the results of the second cycle when assistance is made plans to improve quality, to reach the percentage value of the fifth cycle of the new quality strategy with an increase as an implication of the assistance carried out by the Indraprasta PGRI University Jakarta Community Service Lecturer Team